Radykalizm kulturowy ubiegłego stulecia - Smaga, Józef (Przegląd Rusycystyczny, 2006)
КУЛЬТУРНЫЙ РАДИКАЛИЗМ ПРОШЛОГО СТОЛЕТИЯ Резюме Из первого послания святого апостола Иоанна Богослова (5–19) следует, «что весь мир лежит во зле». В этой связи необходимости преодоления последствий людоеских тоталитаризмов ХХ столетия должно сопутствовать сознание имманетной порочности человеической природы. Во избежание ситуации, когда «экстремизм» терапии может повторять «экстремизм» самой болезни. CULTURAL RADICALISM OF THE LAST CENTURY Summary From St John’s First Letter (5–19) comes that ‘the whole world is seated in wickedness.’ Thus, the necessity for overcoming of the results of genocidal totalitarianisms of the 20th century ought to be accompanied by consciousness of the immanent sinfulness of the human nature so that in the battle against evil possible ‘extremism’/ radicalism of the therapy should not worsen the extremism of the disease itself.